Molecular Pathways Involved in Pregnancy-Induced Prevention Against Breast Cancer - Barton, Maria; Santucci-Pereira, Julia; Russo, Jose (Frontiers in Endocrinology, 2014)
Pregnancy produces a protective effect against breast cancer in women who had their first full term pregnancy (FTP) in their middle twenties. The later in life the first delivery occurs, the higher the risk of breast cancer development. Also, transiently during the postpartum period, the risk of developing breast cancer increases. This transient increased risk is taken over by a long-lasting protective period. The genomic profile of parous women has shown pregnancy induces a long-lasting “genomic signature” that explains the preventive effect on breast cancer. This signature reveals that chromatin remodeling is the driver of the differentiation process conferred by FTP. The chromatin remodeling process may be the ultimate step mediating the protection of the breast against developing breast cancer in post-menopausal years.